Kajian Implementasi Mutu dengan Pendekatan Integrasi Six Sigma dan TQM Melalui Penilaian Malcolm Baldridge di Rumah Sakit Charitas Palembang - Manurung, Jessihana Morgan (UI Scholars Hub, 2017)
Hospitals increasingly are expected to provide better health services (Muchtar, 2011). Excellent service and quality have an impact on customer satisfaction and loyalty. One measure of quality achievement is customer loyalty. Charitas Hospital had a decline in customer loyalty from 2013 to 2015 by 80%. It was determined by a decrease in the quality indicators that BOR, LOS, TOI, GDR, NDR which dropped on the last three years (Data RS-Caritas, 2016). Quality management TQM and Six Sigma respectively conceptually and empirically proven as a quality improvement method to improve organizational performance. How is the quality of service at the Charitas Hospital observed from the criteria Malcolm Baldrige Criteria with the integration of TQM and Six Sigma approach?